Construction and Negotiation of Power in Communicative Interaction: Systematic Literature Review in Communication Psychology - Jaka Farih Agustian; Andria Saptyasari; Silviana Purwanti (About the Journal, 2026)
Communication is a fundamental mechanism through which identity, social relationships, and power are constructed and negotiated through dynamic psychological and interactional processes, particularly within increasingly complex digital and institutional environments. Although research on communication and power has expanded significantly, conceptual fragmentation remains, and the integration of communication psychology perspectives explaining how power, identity, legitimacy, and influence are negotiated through communicative interaction is still limited. This study aims to integrate existing research to identify conceptual patterns, thematic developments, and psychological mechanisms underlying power negotiation, identity construction, and legitimacy in communication processes. This study employed a systematic literature review of 37 Scopus-indexed journal articles published between 2013 and 2026, focusing on communication psychology, identity construction, symbolic communication, authenticity, visibility, and negotiation. The analysis followed structured stages of identification, screening, eligibility assessment, and conceptual synthesis, supported by bibliometric analysis to examine publication trends, citation impact, and author contributions. The findings indicate a significant increase in scientific production, with an annual growth rate of 53.61% and an average of 131.27 citations per document, demonstrating strong academic relevance and impact. Communicative power is constructed through discursive strategies, conversational control, framing, and linguistic choices mediated by cognitive processes, perception, and psychological interpretation. Communication also plays a central role in negotiating identity, legitimacy, and social positioning across interpersonal, institutional, and digital contexts. This study contributes theoretically by integrating communication psychology perspectives and provides practical implications for improving communicative effectiveness and social legitimacy in contemporary societyKomunikasi merupakan mekanisme fundamental dalam membentuk identitas, relasi sosial, dan konstruksi kekuasaan melalui proses psikologis dan interaksional yang dinamis, terutama dalam konteks digital dan institusional yang semakin kompleks. Meskipun penelitian tentang komunikasi dan kekuasaan telah berkembang pesat, masih terdapat fragmentasi konseptual dan keterbatasan integrasi perspektif psikologi komunikasi dalam menjelaskan bagaimana kekuasaan, identitas, legitimasi, dan pengaruh dinegosiasikan melalui interaksi komunikatif. Penelitian ini bertujuan untuk mengintegrasikan temuan penelitian sebelumnya guna mengidentifikasi pola konseptual, perkembangan tematik, dan mekanisme psikologis yang mendasari negosiasi kekuasaan, konstruksi identitas, dan legitimasi melalui komunikasi. Penelitian ini menggunakan metode systematic literature review terhadap 37 artikel jurnal terindeks Scopus yang diterbitkan antara tahun 2013 hingga 2026, dengan fokus pada psikologi komunikasi, konstruksi identitas, komunikasi simbolik, autentisitas, visibilitas, dan negosiasi. Analisis dilakukan secara sistematis melalui tahapan identifikasi, seleksi, evaluasi kelayakan, dan sintesis konseptual, serta didukung analisis bibliometrik untuk mengidentifikasi tren publikasi, dampak sitasi, dan kontribusi penulis. Hasil penelitian menunjukkan bahwa produksi ilmiah meningkat signifikan dengan tingkat pertumbuhan tahunan sebesar 53,61% dan rata-rata sitasi sebesar 131,27 per dokumen, menunjukkan relevansi dan dampak akademik yang tinggi. Kekuasaan komunikatif dikonstruksi melalui strategi diskursif, pengelolaan percakapan, framing, dan pilihan linguistik yang dimediasi oleh proses kognitif, persepsi, dan interpretasi psikologis. Komunikasi juga berperan penting dalam negosiasi identitas, legitimasi, dan posisi sosial dalam konteks interpersonal, institusional, dan digital. Penelitian ini memberikan kontribusi teoritis dalam mengintegrasikan perspektif psikologi komunikasi serta implikasi praktis untuk meningkatkan efektivitas komunikasi dan legitimasi sosial dalam masyarakat kontemporer.